The Right of Residence of Third Country Spouses who Became Victims of Domestic Violence in the Scope of Application of the Free Movement Directive – Legal Analysis of the NA Case - Gyeney, Laura (Pécs journal of international and European law, 2018)
The NA case focuses on the right to remain in a host Member State for the TCN spouse of a migrant Union citizen who fell victim of domestic violence during their marriage with the Union citizen, but where the abuser had left the member state in question before the dissolution of the marriage. The case reveals gap in the relevant EU framework, while it provides an opportunity to examine the broader question of the relation between supranational citizenship and the rights of TCNs under EU law.